Extraction of chitosan, characterisation and its use for water purification - Alaa Jabbar Al-Manhel; Asaad Rehman Saeed Al-Hilphy; Alaa Kareem Niamah (Journal of the Saudi Society of Agricultural Sciences)
This study was carried out in the Food Science Department, Agriculture College, Basrah University to investigate the effect of different chitosan concentrations on drinking water quality. The studied parameters were turbidity, TDS, electrical conductivity and pH. The results showed that the turbidity, TDS, electrical conductivity and pH have been decreased with the increase of chitosan concentration. When chitosan concentration increased from 0 to 1 g 100 ml−1, the turbidity, TDS, electrical conductivity and pH were decreased from 1.98 to 0.98 NTU, 5.67 to 4.13 g L−1, 10.18 to 5.27 mS cm−1, 6.1 to 5.71 respectively. The linear equations have represented the relationship between all parameters and chitosan concentration. However, the total bacteria count, total coliform bacteria, Staphylococci, Fecal coliform bacteria and Vibrio spp. have been eliminated completely by using Chitosan concentration of 0.8, 0.4, 0.8, 0.2 and 0.2 g 100 ml−1 respectively. Keywords: Shrimp shell, Chitosan, Characterisation, Water treatment, Water quality